(untitled) (Journal of Libya for geographical studies, 2024)
Education is a basic need of the population, as the progress and development of any city or country is based on it. Geographic information systems have assisted the tasks of planners in terms of making decisions regarding the development and distribution of many different institutions and solving many problems. This study aims to know the patterns of geographical distribution of secondary education schools in the city of Bani Walid, and to The reality of the spatial distribution of these schools in the city, using Geographic Information Systems (GIS) technology, and to interpret the pattern of spatial distribution. The study follows the descriptive and analytical approach, such as analyzing the standard distance, the average geographical center, and the direction of distribution. The nearest neighbor factor, the scope of service in the city of Bani Walid, and the extent to which planning standards are applied to secondary education schools in the city of Bani Walid.